Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1515/jpem-2015-0171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylphenidate on appetite and growth in children diagnosed with attention deficit and hyperactivity disorder

Abstract: The purpose of this study was to determine the levels of leptin, ghrelin, and nesfatin-1 to elucidate the causes of poor appetite and growth retardation in patients receiving methylphenidate therapy for attention deficit hyperactivity disorder. The study was performed on 89 male subjects; 48 patients and 41 healthy controls, aged 7-14 years. Following treatment, patients' leptin levels increased and ghrelin levels decreased while no significant change was found in nesfatin-1 levels. Of the 48 patients, 34 deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…However, this may be due to the simultaneous effect of diabetes therapy on weight gain in this group of patients 35 or psychosocial confounders. 36 Our results are in line with a previous report by Gurbuz et al 37 In their study, 34 patients with ADHD out of 48 developed lack of appetite during treatment with methylphenidate.…”
Section: Discussionsupporting
confidence: 93%
“…However, this may be due to the simultaneous effect of diabetes therapy on weight gain in this group of patients 35 or psychosocial confounders. 36 Our results are in line with a previous report by Gurbuz et al 37 In their study, 34 patients with ADHD out of 48 developed lack of appetite during treatment with methylphenidate.…”
Section: Discussionsupporting
confidence: 93%
“…16 Bununla birlikte diğer çalışmalardan farklı olarak, bir çalışmada tedavi öncesi DEHB grubunda kontrol grubuna göre grelin düzeyinin anlamlı olarak yüksek olduğu da bildirilmiştir. 17 Aynı çalışmada üç aylık MPH tedavisi sonrası grelin düzeyinin tedavi öncesine göre anlamlı oranda düştüğü bulunmuştur. Bizim çalışmamız-da yeni tanı konan DEHB'li hastalar ile sağlıklı kontrol grubu arasında grelin düzeylerinde farklı-lık olmadığı bulundu.…”
Section: Npy Leptin Ve Grelin Düzeylerinin Değerlen-dirilmesiunclassified
“…16 Bir başka çalış-mada, DEHB'li erkek çocuklarda tedavi sonrası leptin düzeyi tedavi öncesi leptin düzeyine göre istatistiksel olarak yüksek bulunmuştur. 17 DEHB'li 33 erkek çocukta tedavi öncesi ve iki aylık tedavi sonrası grelin düzeylerinin değerlen-dirildiği bir çalışmada, tedavi öncesi ve tedavi sonrası grelin düzeyleri arasında fark olmadığı belirtilmiştir. 18 Diğer bir çalışmada, MPH tedavisi öncesi DEHB grubu ile sağlıklı kontrol grubu arasında grelin düzeyleri arasında farklılık olmadığı, iki aylık MPH tedavi sonrasında ise grelin düzeylerinin arttığı saptanmıştır.…”
Section: Introductionunclassified
“…It has also been proposed that the appetite changes associated with stimulant medications may play a role in altering growth patterns. Gurbuz et al evaluated hormones associated with appetite regulation (9). They reported that after treatment with methylphenidate, levels of leptin (an appetite-suppressing hormone) increased, and levels of ghrelin (an appetite-stimulating hormone) decreased significantly.…”
Section: Stimulant Medicationsmentioning
confidence: 99%